Los alfares marrones de los sitios lima. Implicancias de una aproximación arqueométrica a su proveniencia - Vega Centeno Sara Lafosse, Rafael (2022)
We present the results of XRF analyses on a sample of brown wares from Huaca 21 (Middendorf) of the Maranga Complex, which correspond to the Lima culture occupation. The analyses reveal that they are exogenous to Maranga and the coastal region. Furthermore, a formal comparison with ceramics recovered in the middle and upper valleys of Chancay and Chillón suggests that brown wares might have been produced in highland loci and, hence, their presence at Lima sites open a series of inquiries on the nature of coast-highland interactions during the Early Intermediate Period and the beginnings of the Middle Horizon Period in central Perú.